POLITICAL RECRUITMENT OF FEMALE CANDIDATES IN MEETING THE QUOTA POLICY IN THE PROSPEROUS JUSTICE PARTY (PARTAI KEADILAN SEJAHTERA) OF DIY PROVINCE IN 2019 - PURWANINGSIH, TITIN; RUBIYATI, RUBIYATI (Jurnal Studi Pemerintahan, 2019)
Political recruitment  in the Prosperous Justice Party  (Partai Keadilan Sejahtera/PKS) has fulfilled a 30% quota of female candidates, but they seldom to be  elected as legislative members. Political recruitment in meeting the 30% quota of female is inseparable from  supply and demand sides. By using qualitative research methods, political recruitment process is analyzed of supply and demand sides, with data collection techniques by documentation and in-depth interview. The research finding showed that there were shortcomings in the supply side of the recruitment of female candidates, namely the low political experience and motivation of women to get power. This is related to the demand side, where there are still few women who have strategic positions in the party management. This cause of policy making in the party office less supportive of women to be elected.